Principles, power, and politics - Khanna, D. D.; Kueck, Gert W.; Workshop on Principles, Power, and Politics (1998 : Jaipur, India) (Delhi : Macmillan India Ltd., 1999)
Contributed articles presented at the Workshop on Principles, Power, and Politics held in Jaipur in Nov. 1998; predominantly on the context of India.
Keywords: India -- Politics and government